Dare : straight talk on confidence, courage, and career for women in charge - Blalock, Becky, 1955- (San Francisco : Jossey-Bass, 2014)
"From a veteran Fortune 500 executive, how women can reach and succeed in top leadership positionsThough women hold a majority of the managerial and professional jobs in the workforce, they occupy a mere 14% of C-suite positions at Fortune 500 firms. To break through this stubborn glass ceiling, women must learn to take bold steps when career-defining moments arise. During her 33-year career at Southern Company, a Fortune 500 utility company, Becky Blalock rose to become CIO in a traditionally male industry. Now she offers her own hard-won advice, as well as that of 28 top female executives, to show all aspiring women how to dare to reach the highest tier of leadership and C-suite positions. Includes advice and mentoring lessons from top women business leaders such as: Anna Maria Chavez, CEO of the Girl Scouts of the USA; Kat Cole, President of Cinnabon; Carol Tome, CFO of Home Depot; Dr. Beverly Tatum, president of Spelman College, and Jeanette Horan, CIO of IBM, among many others Features straightforward, honest advice on gaining confidence, speaking up, finding mentors, learning to fail, building a network of allies, managing others, and more Written by pioneering business leader Becky Blalock, with a Foreword by Anne Mulcahy, former chairperson and CEO of Xerox Corporation Dare is must-needed guide for women everywhere, at every level, striving to develop the character, skills, and relationships that deliver greater success in the workplace. "--
Includes index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Women executives; Leadership in women; Success in business; Businesswomen; Career development; Electronic books